Preparation and characterization of bovine dental pulp-derived extracellular matrix hydrogel for regenerative endodontic applications: an in vitro study - Hisham Elnawam; Abdelrahman Thabet; Ahmed Mobarak; Amr Abdallah; Rania Elbackly (BMC Oral Health)
Abstract Background The use of biological scaffolds in regenerative endodontics has gained much attention in recent years. The search for a new biomimetic scaffold that contains tissue-specific cell homing factors could lead to more predictable tissue regeneration. The aim of this study was to prepare and characterize decellularized bovine dental pulp-derived extracellular matrix (P-ECM) hydrogels for regenerative endodontic applications. Methods Freshly extracted bovine molar teeth were collected. Bovine dental pulp tissues were harvested, and stored at -40º C. For decellularization, a 5-day protocol was implemented incorporating trypsin/EDTA, deionized water and DNase treatment. Decellularization was evaluated by DNA quantification and histological examination to assess collagen and glycosaminoglycans (GAGs) content. This was followed by the preparation of P-ECM hydrogel alone or combined with hyaluronic acid gel (P-ECM + HA). The fabricated scaffolds were then characterized using protein quantification, hydrogel topology and porosity, biodegradability, and growth factor content using Enzyme-linked immunosorbent assay (ELISA): transforming growth factor beta-1(TGF-β1), basic fibroblast growth factor (bFGF), bone morphogenetic protein 2 (BMP-2) and vascular endothelial growth factor (VEGF). Results Decellularization was histologically confirmed, and DNA content was below (50 ng/mg tissue). P-ECM hydrogel was prepared with a final ECM concentration of 3.00 mg/ml while P-ECM + HA hydrogel was prepared with a final ECM concentration of 1.5 mg/ml. Total protein content in P-ECM hydrogel was found to be (439.0 ± 123.4 µg/µl). P-ECM + HA showed sustained protein release while the P-ECM group showed gradual decreasing release. Degradation was higher in P-ECM + HA which had a significantly larger fiber diameter, while P-ECM had a larger pore area percentage. ELISA confirmed the retention and release of growth factors where P-ECM hydrogel had higher BMP-2 release, while P-ECM + HA had higher release of TGF-β1, bFGF, and VEGF. Conclusions Both P-ECM and P-ECM + HA retained their bioactive properties demonstrating a potential role as functionalized scaffolds for regenerative endodontic procedures.